Simulation Evidence and Analysis of Alternative Methods of Evaluating Dollar-Unit Samples - Grimlund, Richard A.; Felix, William L. (The Accounting Review, 1987)
[Several new methods of evaluating dollar-unit samples have been proposed recently for use in auditing. This paper presents results of a simulation study that compared four of these new methods. Additional simulations on alternative forms of two of these are also presented. Evidence on the reliability and relative size of the upper error bounds for each method is provided for 2,160 different combinations of sample sizes, confidence levels, and types of accounting populations. The results provide a comprehensive analysis of the capabilities of these methods. All four methods have strengths and weaknesses. The Multinomial Dirichlet bound is quite reliable but very conservative and (as formulated) not able to utilize understatement errors. The two versions of the Cox and Snell bound that were tested (with different priors) varied considerably in their reliability over a range of confidence levels. While not without an occasional reliability problem, test results for the Moment Method bound and one of the two Bayesian-Normal bounds were largely favorable.]